NEGRI, A. (2019). Marx y Foucault. Buenos Aires: Editorial Cactus, 255 páginas. - Jimenez Morales, Luis Alberto (Daimon Revista Internacional de Filosofia, 2022)
Reseña de NEGRI, A. (2019). Marx y Foucault. Buenos Aires: Editorial Cactus, 255 páginas.